Organic Geochemistry of the Hot Shale Member of the Tanez-zuft Formation of wells B1-23 and Q1-23, Ghadames Basin, NW Libya with Regional Correlation - Abdulhamid Boshnyif; Osama Shaltami; Anis Belhaj; Mustafa Ben Hkoma (AlQalam Journal of Medical and Applied Sciences, 2025)
The present work is a source rock assessment of the Hot Shale Member of the Tanezzuft Formation (Early Silurian) using data obtained from wells B1-23 and Q1-23, Ghadames Basin, NW Libya. The geochemical data obtained from HAWK instrument analysis done by Sirte Oil Company on a number of shale samples representing the Hot Shale Member. In terms of organic richness, the Hot Shale Member falls between good and excellent based on the TOC values (1.05-12.39%). The binary plot of TOC versus PP backs up this assumption. In terms of kerogen type, the HI values (126-794 mg/g) display the ex-istence of different types of kerogens, such as types I, II, and III. The binary plots of Tmax versus HI, TOC versus S2, and OI versus HI offer more proof for this hypothesis. In terms of indigeneity, the dominance of indigenous hydrocarbons is suggested by the S1/TOC ratio (0.16-0.81). The binary plot of TOC versus S1 lends credence to this assumption. In terms of thermal maturity, the values of Tmax (417-441 oC) and Ro (0.3-0.78%), and the binary plots of Tmax versus HI, Tmax versus Ro, and PI versus Tmax indicate that the samples of well Q1-23 are primarily contain mature organic matter, whereas the majority of the samples of well B1-23 contain immature organic matter. In terms of petroleum potential, the Hot Shale Member exhibits a variety of petroleum potential, as shown by the binary plot of TOC versus HI. In terms of kinetic parameters, the activation energies (47-84 kcal/mol) have a gaussian shape.